Handbook of prenatal diagnosis (Cambridge University Press, 1995)
This book provides an outline of current science and practice in the area of prenatal diagnosis, explaining the techniques available, their indications, clinical use, and complications. Tables and illustrations clarify the principles and demonstrate the findings for each method of prenatal diagnosis. The volume also covers the diagnosis of infectious disease in the fetus and neonate and laboratory screening tests for the newborn (in an Appendix). The authors discuss educational, counseling and ethical issues and include a chapter devoted to the needs of parents and families as consumers of these expanding services. This volume will serve as an important practical resource for all the health professionals now involved in prenatal diagnosis